2004
DOI: 10.1056/nejmoa032454
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Skin Papillomas with Topical α-Lactalbumin–Oleic Acid

Abstract: Treatment with topical alpha-lactalbumin-oleic acid has a beneficial and lasting effect on skin papillomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
145
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 179 publications
(150 citation statements)
references
References 21 publications
2
145
0
3
Order By: Relevance
“…The MG state is characterized by the absence of long-lived tertiary structure, but it still contains a high degree of secondary structure (20,21), with a radius of gyration only Ϸ10% larger than the native state (22,23). The MG state of ␣-lactalbumin has recently attracted considerable interest when it was realized that it may act as an important component causing apoptosis of tumor cells (24).…”
Section: Conformational Transition Kinetics Of ␣-Lactalbumin From An mentioning
confidence: 99%
“…The MG state is characterized by the absence of long-lived tertiary structure, but it still contains a high degree of secondary structure (20,21), with a radius of gyration only Ϸ10% larger than the native state (22,23). The MG state of ␣-lactalbumin has recently attracted considerable interest when it was realized that it may act as an important component causing apoptosis of tumor cells (24).…”
Section: Conformational Transition Kinetics Of ␣-Lactalbumin From An mentioning
confidence: 99%
“…We have shown that the partially unfolded form of the human protein attains a new function when bound to oleic acid [1]. HAMLET kills tumor cells in vitro and the anti-tumor activity is retained in vivo, in a brain tumor model and in patients with skin papillomas [24,25]. This study examined if α -lactalbumins from different species can form HAMLET-like with similar biological activity as HAMLET.…”
Section: Can Hamlet-like Complexes Be Formed From Casein If Oleic Acimentioning
confidence: 99%
“…HAMLET showed promising healing results in vivo when tested as topical application on human skin papillomas [3], on human glioblastoma xenografts in a rat model [4] and by intravesical HAMLET instillations in both mice and humans with bladder cancer [5,6].…”
Section: Introductionmentioning
confidence: 99%